The Impact of Social Media Marketing on Celkeku Purchase Decision Through Brand Image and Brand Awareness - Sherina Eklezia; Fahrul Riza; Endi Sarwoko (Green Publisher Indonesia, 2025)
With the rapid growth of digital business, Micro, Small, and Medium Enterprises (MSMEs) must adapt their marketing strategies, particularly through Social Media Marketing (SMM), to remain competitive and increase market visibility. Despite their significant contribution to Indonesia’s economy, many MSMEs face challenges in effectively leveraging SMM. This study examines the impact of SMM on Brand Image (BI), Brand Awareness (BA), and Purchase Decision (KP) using Celkeku, an online cake shop, as the research object. Data were collected via a survey of 150 Celkeku customers and analyzed using Structural Equation Modeling (SEM) to evaluate relationships among variables. The findings show that SMM positively influences BI and BA, but BA does not significantly affect KP. Instead, BI serves as a mediating variable that strengthens the influence of SMM on KP, highlighting the crucial role of brand image in consumers’ purchase decisions. This study supports the Theory of Planned Behavior and Consumer Decision-Making Theory within the context of digital marketing for MSMEs. Moreover, the results suggest that enhancing brand awareness alone is insufficient; MSMEs must prioritize strengthening brand image and delivering quality customer experiences to build trust, satisfaction, and product differentiation, which subsequently impact purchase decisions. Limitations include the cross-sectional design, a sample limited to Celkeku customers, and potential respondent bias. Future research is recommended to adopt mixed methods to explore psychological and emotional factors influencing purchasing decisions in digital businesses.